Factors Associated with Blood Culture Contamination in the Emergency Department: Critical Illness, End-Stage Renal Disease, and Old Age. - Chih-Jan Chang; Chi-Jung Wu; Hsiang-Chin Hsu; Chiu-Hui Wu; Fang-Ying Shih; Shou-Wen Wang; Yi-Hui Wu; Chia-Ming Chang; Yi-Fang Tu; Chih-Hsien Chi; Hsin-I Shih (PLoS ONE, 2015)
Background Blood culture contamination in emergency departments (ED) that experience a high volume of patients has negative impacts on optimal patient care. It is therefore important to identify risk factors associated with blood culture contamination in EDs. Methodology/principal findings A prospectively observational study in a university-affiliated hospital were conducted between August 2011 and December 2012. Positive monomicrobial and negative blood cultures drawn from adult patients in the ED were analyzed to evaluate the possible risk factors for contamination. A total of 1,148 positive monomicrobial cases, 391 contamination cases, and 13,689 cases of negative blood culture were identified. Compared to patients with negative blood cultures, patients in triage levels 1 and 2 (Incidence Rate Ratio, IRR = 2.24), patients with end-stage renal disease (ESRD) (IRR = 2.05), and older patients (IRR: 1.02 per year) were more likely to be associated with ED blood culture contamination. Conclusions/significance Critical patients (triage levels 1 and 2), ESRD patients, and older patients were more commonly associated with blood culture contamination in the ED. Further studies to evaluate whether the characteristics of skin commensals contribute to blood culture contamination is warranted, especially in hospitals populated with high-risk patients.